Glass ceramic ware with excellent thermal shock resistance and preparation method thereof
By coating nanosilver-silicon composite sol and agated cuprous oxide-loaded glass fiber composite coating on the microcrystalline glass matrix, the shortcomings of microcrystalline glassware in terms of thermal shock and antibacterial properties are solved, and excellent thermal shock and antibacterial effects are achieved.
Patent Information
- Application Number
- CN202411756845.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing microcrystalline glassware has shortcomings in thermal shock resistance and antibacterial properties, which leads to prone to cracks in high temperature environments and lacks effective antibacterial functions, which limits its application in food safety and health.
A composite coating was prepared by using nanosilver-silicon composite sol and aminated copper oxide-loaded glass fibers and other materials, and coated on the surface of the microcrystalline glass matrix. After curing, a microcrystalline glassware with excellent thermal shock resistance and antibacterial properties were obtained.
It significantly improves the thermal shock and antibacterial properties of microcrystalline glassware, and enhances its stability and food safety in high temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microcrystalline glass, and in particular to a microcrystalline glass vessel with excellent thermal shock resistance and a preparation method thereof. Background Art
[0002] Due to its excellent physical and chemical properties, glass-ceramics has superior performance in thermal shock stability and mechanical strength compared to traditional glass and ceramics. However, the widespread application of glass-ceramics still faces some challenges, especially in terms of thermal shock resistance and antibacterial properties. Insufficient thermal shock resistance may cause cracks in utensils under high temperature environments, thus affecting safety of use. In addition, with the enhancement of hygiene awareness, the demand for antibacterial materials in homes and public places continues to increase. Existing glass-ceramics utensils generally lack effective antibacterial functions, which limits their application in food safety and health.
[0003] In order to solve the above problems and improve the antibacterial property of microcrystalline glass, the present invention provides a microcrystalline glass vessel with excellent thermal shock resistance and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a microcrystalline glass vessel with excellent thermal shock resistance and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a microcrystalline glass vessel with excellent thermal shock resistance comprises the following steps: Step 1: Take nano silver-silicon composite sol, amination-loaded cuprous oxide-loaded glass fiber, and deionized water, stir evenly to obtain a composite coating; Step 2: Take silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide, grind for 30-40 minutes, and keep warm at 1600-1650° C. for 3-4 hours to obtain molten glass liquid; Step 3: pour the glass liquid into the mold and cool it to form, anneal and keep it at 600-650℃ for 4-5h, cool it to 30-35℃, nucleate it for 4-6h, crystallize it for 2-3h, and cool it to 25-30℃ to obtain a microcrystalline glass matrix; Step 4: coating the composite coating on the surface of the microcrystalline glass substrate and curing it to obtain a microcrystalline glass vessel with thermal shock resistance.
[0006] More optimally, the method for preparing the amination-loaded cuprous oxide glass fiber comprises the following steps: S1: Take glucose and deionized water, stir evenly to obtain a glucose aqueous solution; take copper acetate monohydrate and ethanol, stir evenly, add modified glass fiber, ultrasonically disperse, heat to 60-65°C, add glucose aqueous solution, stir evenly, add sodium hydroxide solution, precipitate, wash, and dry to obtain glass fiber loaded with cuprous oxide; S2: Take 3-aminopropyltriethoxysilane and toluene, stir evenly, add glass fiber loaded with cuprous oxide, heat to 80-85°C and reflux for 12-14h, wash, filter and dry to obtain amino-loaded glass fiber loaded with cuprous oxide.
[0007] More optimally, the preparation method of the modified glass fiber is: ultrasonically disperse the glass fiber and acetone for 10-15 minutes, let it stand for 10-12 hours, take it out, dry it, add a mixed solution of concentrated sulfuric acid and hydrogen peroxide, stir it for 8-10 hours, wash it, filter it, and dry it to obtain the pretreated glass fiber; take the pretreated glass fiber and ethanol, ultrasonically disperse it, add octadecyltrichlorosilane, stir it for 3-4 hours, wash it, and dry it to obtain the modified glass fiber.
[0008] More optimally, the preparation method of the nano silver-silicon composite sol is: mix tetraethyl orthosilicate and anhydrous ethanol evenly to obtain a tetraethyl orthosilicate solution; take polyvinyl pyrrolidone, deionized water, and anhydrous ethanol, mix evenly, ultrasonicate for 5-10 minutes, add the tetraethyl orthosilicate solution, mix evenly, ultrasonicate to obtain a precursor solution, add nitric acid dropwise, adjust the pH value to 2-4, heat to 80-84°C, react for 3-3.5 hours, and obtain silica sol; take silica sol and nano silver, stir evenly, and obtain a nano silver-silicon composite sol.
[0009] More optimally, the preparation method of the amino-modified chitosan is: take triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add chitosan, heat and reflux for 4-5 hours, cool, filter, wash and dry to obtain amino-modified chitosan.
[0010] More optimally, the microcrystalline glass matrix includes the following components, calculated in molar percentage: 20mol%-22mol% aluminum oxide, 8mol%-10mol% lithium oxide, 3mol%-6mol% zinc oxide, 2.5mol%-3.5mol% titanium dioxide, 0.5mol%-2.0mol% magnesium oxide, 0.4mol%-0.6mol% phosphorus pentoxide, 0.2mol%-0.5mol% zirconium dioxide, 0.1mol%-0.2mol% antimony trioxide, and the rest is silicon dioxide.
[0011] More optimally, the particle size of the silica sol is 3-8 nm.
[0012] More optimally, the average particle size of the nanosilver is 20 nm.
[0013] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide as raw materials to prepare a microcrystalline glass substrate with excellent thermal shock resistance, and then coats the substrate with a composite coating with antibacterial properties to enhance its antibacterial properties.
[0014] (2) The silica sol prepared by the present invention has a particle size between 3 and 8 nm. The silica sol has good dispersibility and can form a more uniform coating. However, the surface area is large, the contact area with the corrosive medium increases, and the corrosion resistance is poor. The present invention adds nanosilver with an average particle size of 20 nm to enhance the antibacterial property of the microcrystalline glassware.
[0015] (3) The present invention uses triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to modify chitosan, thereby increasing the amino content in chitosan and preparing an amino-modified chitosan, which is added to the nanosilver-silicon composite sol to improve the antibacterial property of the composite sol.
[0016] (4) The present invention composites cuprous oxide with glass fiber. The addition of cuprous oxide enhances the antibacterial property of the glass fiber loaded with cuprous oxide. Then, 3-aminopropyltriethoxysilane is used to modify the glass fiber loaded with cuprous oxide so that the surface of the glass fiber loaded with cuprous oxide carries amino groups. At this time, the amino groups on the amination-loaded glass fiber loaded with cuprous oxide have good compatibility with the nanosilver-silicon composite sol carrying amino groups, thereby enhancing the dispersibility of the amination-loaded glass fiber loaded with cuprous oxide and further enhancing the antibacterial property of the microcrystalline glassware. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] There is no special restriction on the purchasing manufacturers of all raw materials involved in the present invention, and illustratively include: glass fiber diameter: 3-10μm; silicon dioxide: 5-100μm; aluminum oxide: 5-100μm; lithium oxide: 5-500μm, zinc oxide: 0.1-10μm, titanium dioxide: 10-200nm, magnesium oxide: 5-50μm; phosphorus pentoxide 5-100μm; zirconium dioxide: 5-100μm; antimony trioxide: 5-100μm; nanosilver: can be purchased from Beijing Zhongke Yannuo New Material Technology Co., Ltd., model: DK101-1, average particle size: 20nm; large particle size silica sol: can be purchased from Zhejiang Delixin Micro-Nano Technology Co., Ltd., model: JN60-40 / 1, particle size: 55-65nm.
[0019] Embodiment 1: A method for preparing a glass-ceramic vessel with excellent thermal shock resistance, comprising the following steps: Step 1: Preparation of amination-loaded cuprous oxide glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 12 min, allowed to stand for 11 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 9 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 3.5 h, wash and dry to obtain modified glass fiber; Take 3.6g of glucose and 100mL of deionized water, stir evenly to obtain a glucose aqueous solution; take 2g of copper acetate monohydrate and 50mL of ethanol, stir evenly, add 4g of modified glass fiber, ultrasonically disperse, heat to 62°C, add the glucose aqueous solution, stir evenly, add 0.3mol / L of sodium hydroxide solution, precipitate, wash, and dry to obtain a glass fiber loaded with cuprous oxide; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of glass fiber loaded with cuprous oxide, heat to 82°C and reflux for 13h, wash, filter and dry to obtain amination-loaded glass fiber with cuprous oxide; Step 2: Preparation of amino-modified chitosan: Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 5 g of chitosan, heat and reflux for 4.5 h, cool, filter, wash and dry to obtain amino-modified chitosan; Step 3: Preparation of nanosilver-silicon composite sol: 30g of tetraethyl orthosilicate and 50g of anhydrous ethanol were mixed evenly to obtain a tetraethyl orthosilicate solution; 1.7g of polyvinyl pyrrolidone, 25g of deionized water and 10g of anhydrous ethanol were mixed evenly, ultrasonicated for 8min, and the tetraethyl orthosilicate solution was added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid was added dropwise, the pH value was adjusted to 3, the temperature was raised to 82°C, and the reaction was carried out for 3.2h to obtain a silica sol with a particle size of 3-8nm; Take 30g silica sol, 3.5g nanosilver, and 1.2g amino-modified chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 4: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino-loaded cuprous oxide glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 5: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were taken, ground for 35 minutes, and kept at 1620°C for 3.5 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, in molar percentage: 21 mol% of aluminum oxide, 9 mol% of lithium oxide, 5 mol% of zinc oxide, 3 mol% of titanium dioxide, 1.0 mol% of magnesium oxide, 0.5 mol% of phosphorus pentoxide, 0.3 mol% of zirconium dioxide, 0.15 mol% of antimony trioxide, and the rest is silicon dioxide; The glass liquid was poured into a mold and cooled to form, annealed at 620°C for 4.5 hours, cooled to 32°C, nucleated for 5 hours, crystallized for 2.5 hours, and cooled to 28°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0020] Embodiment 2: A method for preparing a glass-ceramic vessel with excellent thermal shock resistance, comprising the following steps: Step 1: Preparation of amination-loaded cuprous oxide glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 10 min, allowed to stand for 10 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 8 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 3 h, wash and dry to obtain modified glass fiber; Take 3.6g of glucose and 100mL of deionized water, stir evenly to obtain a glucose aqueous solution; take 2g of copper acetate monohydrate and 50mL of ethanol, stir evenly, add 4g of modified glass fiber, ultrasonically disperse, heat to 60°C, add the glucose aqueous solution, stir evenly, add 0.3mol / L of sodium hydroxide solution, precipitate, wash, and dry to obtain a glass fiber loaded with cuprous oxide; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of glass fiber loaded with cuprous oxide, heat to 80°C and reflux for 12h, wash, filter and dry to obtain amination-loaded glass fiber with cuprous oxide; Step 2: Preparation of amino-modified chitosan: Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 5 g of chitosan, heat and reflux for 4 h, cool, filter, wash and dry to obtain amino-modified chitosan; Step 3: Preparation of nanosilver-silicon composite sol: 30g of tetraethyl orthosilicate and 50g of anhydrous ethanol were mixed evenly to obtain a tetraethyl orthosilicate solution; 1.7g of polyvinyl pyrrolidone, 25g of deionized water and 10g of anhydrous ethanol were mixed evenly, ultrasonicated for 5min, and the tetraethyl orthosilicate solution was added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid was added dropwise, the pH value was adjusted to 2, the temperature was raised to 80°C, and the reaction was carried out for 3h to obtain a silica sol with a particle size of 3-8nm; Take 30g silica sol, 3.5g nanosilver, and 1.2g amino-modified chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 4: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino-loaded cuprous oxide glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 5: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were taken, ground for 30 minutes, and kept at 1600°C for 3 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, calculated by molar percentage: 20 mol% of aluminum oxide, 8 mol% of lithium oxide, 3 mol% of zinc oxide, 2.5 mol% of titanium dioxide, 0.5 mol% of magnesium oxide, 0.4 mol% of phosphorus pentoxide, 0.2 mol% of zirconium dioxide, 0.1 mol% of antimony trioxide, and the remainder is silicon dioxide; The glass liquid is poured into a mold and cooled to form, annealed at 600°C for 4 hours, cooled to 30°C, nucleated for 4 hours, crystallized for 2 hours, and cooled to 25°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0021] Embodiment 3: A method for preparing a glass-ceramic vessel with excellent thermal shock resistance, comprising the following steps: Step 1: Preparation of amination-loaded cuprous oxide glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 15 min, allowed to stand for 12 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 10 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 4 h, wash and dry to obtain modified glass fiber; Take 3.6g of glucose and 100mL of deionized water, stir evenly to obtain a glucose aqueous solution; take 2g of copper acetate monohydrate and 50mL of ethanol, stir evenly, add 4g of modified glass fiber, ultrasonically disperse, heat to 65°C, add the glucose aqueous solution, stir evenly, add 0.3mol / L of sodium hydroxide solution, precipitate, wash, and dry to obtain glass fiber loaded with cuprous oxide; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of glass fiber loaded with cuprous oxide, heat to 85°C and reflux for 14h, wash, filter and dry to obtain amination-loaded glass fiber with cuprous oxide; Step 2: Preparation of amino-modified chitosan: Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 5 g of chitosan, heat and reflux for 5 h, cool, filter, wash and dry to obtain amino-modified chitosan; Step 3: Preparation of nanosilver-silicon composite sol: 30g of tetraethyl orthosilicate and 50g of anhydrous ethanol were mixed evenly to obtain a tetraethyl orthosilicate solution; 1.7g of polyvinyl pyrrolidone, 25g of deionized water and 10g of anhydrous ethanol were mixed evenly, ultrasonicated for 10min, the tetraethyl orthosilicate solution was added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid was added dropwise, the pH value was adjusted to 4, the temperature was raised to 84°C, and the reaction was carried out for 3.5h to obtain a silica sol with a particle size of 3-8nm; Take 30g silica sol, 3.5g nanosilver, and 1.2g amino-modified chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 4: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino-loaded cuprous oxide glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 5: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were ground for 40 minutes and kept at 1650°C for 4 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, calculated by molar percentage: 22 mol% of aluminum oxide, 10 mol% of lithium oxide, 6 mol% of zinc oxide, 3.5 mol% of titanium dioxide, 2.0 mol% of magnesium oxide, 0.6 mol% of phosphorus pentoxide, 0.5 mol% of zirconium dioxide, 0.2 mol% of antimony trioxide, and the remainder is silicon dioxide; The glass liquid is poured into a mold and cooled to form, annealed at 650°C for 5 hours, cooled to 35°C, nucleated for 6 hours, crystallized for 3 hours, and cooled to 30°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0022] Comparative Example 1: Using large-particle silica sol with a particle size of 55-65 nm, the rest is the same as Example 1: Step 1: Preparation of amination-loaded cuprous oxide glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 12 min, allowed to stand for 11 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 9 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 3.5 h, wash and dry to obtain modified glass fiber; Take 3.6g of glucose and 100mL of deionized water, stir evenly to obtain a glucose aqueous solution; take 2g of copper acetate monohydrate and 50mL of ethanol, stir evenly, add 4g of modified glass fiber, ultrasonically disperse, heat to 62°C, add the glucose aqueous solution, stir evenly, add 0.3mol / L of sodium hydroxide solution, precipitate, wash, and dry to obtain a glass fiber loaded with cuprous oxide; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of glass fiber loaded with cuprous oxide, heat to 82°C and reflux for 13h, wash, filter and dry to obtain amination-loaded glass fiber with cuprous oxide; Step 2: Preparation of amino-modified chitosan: Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 5 g of chitosan, heat and reflux for 4.5 h, cool, filter, wash and dry to obtain amino-modified chitosan; Step 3: Preparation of nanosilver-silicon composite sol: Take 30g of large-particle silica sol with a particle size of 55-65nm, 3.5g of nanosilver, and 1.2g of amino-modified chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 4: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino-loaded cuprous oxide glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 5: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were taken, ground for 35 minutes, and kept at 1620°C for 3.5 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, in molar percentage: 21 mol% of aluminum oxide, 9 mol% of lithium oxide, 5 mol% of zinc oxide, 3 mol% of titanium dioxide, 1.0 mol% of magnesium oxide, 0.5 mol% of phosphorus pentoxide, 0.3 mol% of zirconium dioxide, 0.15 mol% of antimony trioxide, and the rest is silicon dioxide; The glass liquid was poured into a mold and cooled to form, annealed at 620°C for 4.5 hours, cooled to 32°C, nucleated for 5 hours, crystallized for 2.5 hours, and cooled to 28°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0023] Comparative Example 2: Chitosan was not amino-modified, and the rest was the same as Example 1: Step 1: Preparation of amination-loaded cuprous oxide glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 12 min, allowed to stand for 11 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 9 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 3.5 h, wash and dry to obtain modified glass fiber; Take 3.6g of glucose and 100mL of deionized water, stir evenly to obtain a glucose aqueous solution; take 2g of copper acetate monohydrate and 50mL of ethanol, stir evenly, add 4g of modified glass fiber, ultrasonically disperse, heat to 62°C, add the glucose aqueous solution, stir evenly, add 0.3mol / L of sodium hydroxide solution, precipitate, wash, and dry to obtain a glass fiber loaded with cuprous oxide; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of glass fiber loaded with cuprous oxide, heat to 82°C and reflux for 13h, wash, filter and dry to obtain amination-loaded glass fiber with cuprous oxide; Step 2: Preparation of nanosilver-silicon composite sol: 30g of tetraethyl orthosilicate and 50g of anhydrous ethanol were mixed evenly to obtain a tetraethyl orthosilicate solution; 1.7g of polyvinyl pyrrolidone, 25g of deionized water and 10g of anhydrous ethanol were mixed evenly, ultrasonicated for 8min, and the tetraethyl orthosilicate solution was added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid was added dropwise, the pH value was adjusted to 3, the temperature was raised to 82°C, and the reaction was carried out for 3.2h to obtain a silica sol with a particle size of 3-8nm; Take 30g silica sol, 3.5g nanosilver, and 1.2g chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 3: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino-loaded cuprous oxide glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 4: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were taken, ground for 35 minutes, and kept at 1620°C for 3.5 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, in molar percentage: 21 mol% of aluminum oxide, 9 mol% of lithium oxide, 5 mol% of zinc oxide, 3 mol% of titanium dioxide, 1.0 mol% of magnesium oxide, 0.5 mol% of phosphorus pentoxide, 0.3 mol% of zirconium dioxide, 0.15 mol% of antimony trioxide, and the rest is silicon dioxide; The glass liquid was poured into a mold and cooled to form, annealed at 620°C for 4.5 hours, cooled to 32°C, nucleated for 5 hours, crystallized for 2.5 hours, and cooled to 28°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0024] Comparative Example 3: No cuprous oxide is added, and the rest is the same as Example 1: Step 1: Preparation of amino glass fiber: 5 g of glass fiber and 200 mL of acetone were ultrasonically dispersed for 12 min, allowed to stand for 11 h, taken out, dried, added with 200 mL of a mixture of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 7:3, stirred for 9 h, washed, filtered, and dried to obtain pretreated glass fiber; Take 4 g of pretreated glass fiber and 500 mL of ethanol, disperse by ultrasonication, add 2 g of octadecyltrichlorosilane, stir for 3.5 h, wash and dry to obtain modified glass fiber; Take 6g of 3-aminopropyltriethoxysilane and 100mL of toluene, stir evenly, add 3g of modified glass fiber, heat to 82°C and reflux for 13h, wash, filter and dry to obtain amino glass fiber; Step 2: Preparation of amino-modified chitosan: Take 90 mL of triethylenetetramine and 15 mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, stir evenly, add 5 g of chitosan, heat and reflux for 4.5 h, cool, filter, wash and dry to obtain amino-modified chitosan; Step 3: Preparation of nanosilver-silicon composite sol: 30g of tetraethyl orthosilicate and 50g of anhydrous ethanol were mixed evenly to obtain a tetraethyl orthosilicate solution; 1.7g of polyvinyl pyrrolidone, 25g of deionized water and 10g of anhydrous ethanol were mixed evenly, ultrasonicated for 8min, and the tetraethyl orthosilicate solution was added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid was added dropwise, the pH value was adjusted to 3, the temperature was raised to 82°C, and the reaction was carried out for 3.2h to obtain a silica sol with a particle size of 3-8nm; Take 30g silica sol, 3.5g nanosilver, and 1.2g amino-modified chitosan, stir evenly to obtain nanosilver-silicon composite sol; Step 4: Preparation of composite coating: Take 33.5g of nano silver-silicon composite sol, 5g of amino glass fiber, and 100mL of deionized water, stir evenly to obtain a composite coating; Step 5: Preparation of thermal shock resistant glass-ceramic vessels: Silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide were taken, ground for 35 minutes, and kept at 1620°C for 3.5 hours to obtain molten glass liquid; The microcrystalline glass matrix comprises the following components, in molar percentage: 21 mol% of aluminum oxide, 9 mol% of lithium oxide, 5 mol% of zinc oxide, 3 mol% of titanium dioxide, 1.0 mol% of magnesium oxide, 0.5 mol% of phosphorus pentoxide, 0.3 mol% of zirconium dioxide, 0.15 mol% of antimony trioxide, and the rest is silicon dioxide; The glass liquid was poured into a mold and cooled to form, annealed at 620°C for 4.5 hours, cooled to 32°C, nucleated for 5 hours, crystallized for 2.5 hours, and cooled to 28°C to obtain a microcrystalline glass matrix; The composite coating is coated on the surface of the microcrystalline glass substrate with a coating thickness of 100 nm, and then cured to obtain a microcrystalline glass vessel with thermal shock resistance.
[0025] experiment: The microcrystalline glassware prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, and a thermal shock test was performed at 700° C. Escherichia coli was used as the bacterial species, and the antibacterial rate of the microcrystalline glassware was tested by the plate method. The data obtained are as follows:
[0026] Conclusion: From the comparison of the data in the table, it can be seen that the comparative example 1 uses a large-particle silica sol with a particle size of 55-65nm, which has poor dispersibility, uneven coating, and the antibacterial property of the microcrystalline glassware is deteriorated. In comparative example 2, chitosan is not amino-modified, and the dispersion of the glass fiber loaded with cuprous oxide is poor, which affects the antibacterial property of the microcrystalline glassware. In comparative example 3, cuprous oxide is not added, and the antibacterial property of the microcrystalline glassware is deteriorated. The silica sol prepared in Examples 1-3 of the present invention has a particle size between 3-8nm, and the silica sol has good dispersibility and can form a more uniform coating, but the surface area is large, the contact area with the corrosive medium is increased, and the corrosion resistance is poor. The present invention adds nanosilver with an average particle size of 20nm to enhance the antibacterial property of the microcrystalline glassware. Chitosan was modified by using triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to increase the amino content in chitosan. An amino-modified chitosan was prepared and added into nanosilver-silicon composite sol to improve the antibacterial property of the composite sol.
[0027] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a glass-ceramic vessel with excellent thermal shock resistance, characterized in that: The following steps are involved: Step 1: Take nano silver-silicon composite sol, amination-loaded cuprous oxide-loaded glass fiber, and deionized water, stir evenly to obtain a composite coating; Step 2: Take silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, titanium dioxide, magnesium oxide, phosphorus pentoxide, zirconium dioxide, and antimony trioxide, grind for 30-40 minutes, and keep warm at 1600-1650° C. for 3-4 hours to obtain molten glass liquid; Step 3: pour the glass liquid into the mold and cool it to form, anneal and keep it at 600-650℃ for 4-5h, cool it to 30-35℃, nucleate it for 4-6h, crystallize it for 2-3h, and cool it to 25-30℃ to obtain a microcrystalline glass matrix; Step 4: coating the composite coating on the surface of the microcrystalline glass substrate and curing it to obtain a microcrystalline glass vessel with thermal shock resistance.
2. The method for preparing a micro-ceramic glass vessel with excellent thermal shock resistance according to claim 1, characterized in that: The preparation method of the amination-supported cuprous oxide glass fiber comprises the following steps: S1: Take glucose and deionized water, stir evenly to obtain a glucose aqueous solution; take copper acetate monohydrate and ethanol, stir evenly, add modified glass fiber, ultrasonically disperse, heat to 60-65°C, add glucose aqueous solution, stir evenly, add sodium hydroxide solution, precipitate, wash, and dry to obtain glass fiber loaded with cuprous oxide; S2: Take 3-aminopropyltriethoxysilane and toluene, stir evenly, add glass fiber loaded with cuprous oxide, heat to 80-85°C and reflux for 12-14h, wash, filter and dry to obtain amino-loaded glass fiber loaded with cuprous oxide.
3. The method for preparing a micro-ceramic glass vessel with excellent thermal shock resistance according to claim 2, characterized in that: The preparation method of the modified glass fiber is as follows: ultrasonically disperse the glass fiber and acetone for 10-15 minutes, stand for 10-12 hours, take out, dry, add a mixed solution of concentrated sulfuric acid and hydrogen peroxide, stir for 8-10 hours, wash, filter, and dry to obtain the pretreated glass fiber; take the pretreated glass fiber and ethanol, ultrasonically disperse, add octadecyltrichlorosilane, stir for 3-4 hours, wash, and dry to obtain the modified glass fiber.
4. The method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to claim 1, characterized in that: The preparation method of the nano silver-silicon composite sol is as follows: tetraethyl orthosilicate and anhydrous ethanol are mixed evenly to obtain a tetraethyl orthosilicate solution; polyvinyl pyrrolidone, deionized water and anhydrous ethanol are mixed evenly, ultrasonicated for 5-10 minutes, the tetraethyl orthosilicate solution is added, mixed evenly, ultrasonically dispersed to obtain a precursor solution, nitric acid is added dropwise, the pH value is adjusted to 2-4, the temperature is raised to 80-84°C, and the reaction is carried out for 3-3.5 hours to obtain a silica sol; the silica sol, nano silver and amino-modified chitosan are mixed evenly to obtain a nano silver-silicon composite sol.
5. The method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to claim 4, characterized in that: The preparation method of the amino-modified chitosan is as follows: triethylenetetramine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are taken, stirred evenly, chitosan is added, heated and refluxed for 4-5 hours, cooled, filtered, washed and dried to obtain the amino-modified chitosan.
6. The method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to claim 1, characterized in that: The microcrystalline glass matrix includes the following components, calculated by molar percentage: 20mol%-22mol% of aluminum oxide, 8mol%-10mol% of lithium oxide, 3mol%-6mol% of zinc oxide, 2.5mol%-3.5mol% of titanium dioxide, 0.5mol%-2.0mol% of magnesium oxide, 0.4mol%-0.6mol% of phosphorus pentoxide, 0.2mol%-0.5mol% of zirconium dioxide, 0.1mol%-0.2mol% of antimony trioxide, and the rest is silicon dioxide.
7. The method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to claim 4, characterized in that: The particle size of the silica sol is 3-8 nm.
8. The method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to claim 4, characterized in that: The average particle size of the nanosilver is 20 nm.
9. A glass-ceramic vessel with excellent thermal shock resistance prepared according to the method for preparing a glass-ceramic vessel with excellent thermal shock resistance according to any one of claims 1 to 8.
Citation Information
Patent Citations
Glass fiber loading cuprous oxide visible light catalyst and application thereof
CN103191738A
Colorful antibacterial nanofiber membrane as well as preparation method and application thereof
CN113186649A
Antibacterial and antiviral mask and preparation method thereof
CN113925240A
Antibacterial anticorrosive paint and preparation method thereof
CN115232534A
Colored microcrystalline glassware and preparation method thereof
CN117720277A